Implementing trauma-informed care through social innovation in child welfare residential treatment centres serving elementary school children - Brend, Denise; Fréchette, Nicolas; Milord-Nadon, Arnaud; Harbinson, Tim; Collin-Vezina, Delphine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2020)
Objectives: This article presents the theoretical basis, initial deployment strategies, and resulting preliminary findings of a program implemented in residential treatment centres (RCs) in child welfare. “Program Penguin” aimed to help workers develop trauma-informed attitudes and implement trauma-informed practices, make the workplace more responsive to the well-being of RC workers, and reduce the use of restraints and seclusion among school-aged children in RCs.Methods: Informed by the theories of complex trauma (National Child Traumatic Stress Network Complex Trauma Task Force, 2003), polyvicitimization (Finkelhor et al., 2007), Attachment, Self-Regulation and Competency (ARC; Blaustein & Kinniburgh, 2018) and Positive Behavioural Interventions and Supports (PBIS; Sugai & Horner, 2002), Program Penguin was developed and deployed using the social innovation approach (Fixsen et al. 2005). The key stages of social innovation will here be used to describe the implementation process.Results: Changes in practices were observed, RC worker attitudes towards trauma-informed care were assessed and showed strong effects between multiple covariables. RC worker support needs were identified, and a reduction in the use of restraints and seclusions was shown. Key strategies towards the development and maintenance of buy-in and meaningful change in practices are also described.Implications: Changes observed at all levels of this implementation suggest Programme Penguin is a promising approach, despite local issues that arose and the challenges inherent to program deployment within child protection settings. It appears a trauma-informed program using positive behavioural approaches and leveraging existing organizational strengths may impact intervention strategies, worker attitudes, and the use of restraints and seclusions against children in RCs.